A Literature Study of the Implementation of Character Education for Elementary School Students : Studi Literatur Implementasi Pendidikan Karakter Siswa Sekolah Dasar - Putri Retno Lestari; Feri Tirtoni (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the implementation process in leadership character education for elementary school students in terms of the performance of school management and the implementation process. The method used in this research is literature study using descriptive research method. The results obtained are that the performance of school management on the implementation of character education for elementary school students goes through 3 stages, namely planning, implementation and evaluation. While in the process of implementing leadership character education for elementary school students, namely in the form of programs to strengthen spiritual attitudes and behavior, learning programs to shape leadership characters, habituation of students through leadership learning, habituation of students to carry out responsibilities, and habituation of students through decision making. The implementation of leadership character education for elementary school students can be applied according to the stages of each implementation process.